Meta-Analisis Pengaruh Blansir terhadap Total Fenolik Buah dan Sayur - Sabila, Maureen; Sugiyono, Sugiyono; Indrasti, Dias; Jayanegara, Anuraga (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
Blanching is the most common pretreatment method for fruits and vegetables to maintain product quality. Numerous studies revealed desirable impacts of the process to total phenolic content, while the others showed opposite results. In addition, some differences in the blanching condition such as methods and classification of fruits and vegetables were also known able to affect total phenolic content. This study aimed to analyze the effect of blanching on total phenolic content in vegetables and fruits through a meta-analysis approach. Study selection was conducted with a PRISMA method. There were 28 articles and 82 data used for meta-analysis. The data were analyzed by Hedges’d to calculate the effect size with confidence interval (CI) utilizing OpenMee software. The result showed that blanching demonstrated significant effects on the rise of total phenolic content (hedges’d[95% CI]: 0.782 [0.037 to 1.527]; p<0.05). Based on fruits and vegetables subgroups, the blanching significantly affected the increase of total phenolic content in leaves (hedges’d[95% CI]: 1.484 [0.185–2.782]) and fruits (hedges’d[95% CI]: 2.504 [0.153–4.854] compared to stems and stalks, fruits as vegetable, shoots and sprouts, pulse, and flowers. Meanwhile, in terms of blanching method subgroups, hot water blanching (hedges’d[95% CI]: 1.096 [0.234–1.959]) had significant effects on the rise of total phenolic content compared to steam blanching. Moreover, this meta-analysis was robust against publication bias.